2021
DOI: 10.3390/molecules26030654
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dimer of Epicatechin from an Endophytic Fungus Curvularia australiensis FC2AP on Acute Toxicity Levels, Anti-Inflammatory and Anti-Cervical Cancer Activity in Animal Models

Abstract: Cervical cancer, as the most frequent cancer in women globally and accounts almost 14% in India. It can be prevented or treated with vaccines, radiation, chemotherapy, and brachytherapy. The chemotherapeutic agents cause adverse post effects by the destruction of the neighboring normal cells or altering the properties of the cells. In order to reduce the severity of the side effects caused by the chemically synthesized therapeutic agents, the current research developed an anti-cancer agent dimer of epicatechin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Moreover, the previous researches in our laboratory on endophytic fungi exhibited antimicrobial, antioxidant, anti-angiogenic and anti-cancer activities from different crude and purified extracts of C. australiensis, Alternaria citrimacularis, Al. alternata and Cladosporium cladosporides (Mani et al, 2015a, b;Mani et al, 2021). Our first report will significantly contribute a vital role in pharma industries in the development of antioxidant and anti-cancer therapeutics.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, the previous researches in our laboratory on endophytic fungi exhibited antimicrobial, antioxidant, anti-angiogenic and anti-cancer activities from different crude and purified extracts of C. australiensis, Alternaria citrimacularis, Al. alternata and Cladosporium cladosporides (Mani et al, 2015a, b;Mani et al, 2021). Our first report will significantly contribute a vital role in pharma industries in the development of antioxidant and anti-cancer therapeutics.…”
Section: Discussionmentioning
confidence: 73%
“…The same anti-inflammatory action was observed in vitro with O. basilicum leaf ethanolic extract on lipopolysaccharide (LPS)-stimulated RAW 264.7 cells by inhibiting NO production [ 106 ]. Moreover, specific pro-inflammatory cytokines (IL-2, IL-β, and TNF-α) and inflammatory mediators (iNOS and NO) were inhibited by the action of O. basilicum methanolic extract [ 107 ]. The observed effects of basil could be attributed to its compounds and those that are in the minority or to the synergy between them.…”
Section: Discussionmentioning
confidence: 99%
“…Matzkin et al [213], reported how anti-inflammatory and antioxidant compounds could exert a beneficial role in the improvement of physio-pathological state of the aged male gonad [214]. Similarly, a dimer of epicatechin from the endophytic fungus Curvularia australiensis reverted the tumorigenic effect of B[a]P exposure in female rats on induced cervical cancer by reducing oxidative stress markers and pro-inflammatory ones, thus ameliorating lesion histopathology [215]. Other authors [216] investigated the molecular mechanisms associated with the cytoprotective effect of quercetin and its metabolites against benzo[a]pyrene (B[a]P), suggesting the involvement of other mechanisms beyond the an-tioxidant activity.…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%